INTEGRATIVE AND PEDAGOGICAL FEATURES OF IMPROVING THE PATRIOTIC COMPETENCE OF FUTURE TEACHERS (American Journal of Interdisciplinary Research and Development, 2023)
The interactive forms, methods and tools developed in the framework of the study, based on the competence-based approach of developing a sense of patriotism, were used in the development of the educational manual "pedagogical science and technology of education". These proposals made it possible to prepare future teachers for educational activities, to develop an active civil position in them.